Ticks species in a protected area of the Autonomous City of Buenos Aires - González, Sandra (2020)
The present study aimed to determine the presence of ticks in the Ecological Reserve Ciudad Universitaria - Costanera Norte, protected natural area of the CABA, close to a highly trafficked urban area. In the period August 2017 to July 2018, 829 Ixodes auritulus (larvae, nymphs, adults) and a nymph of Rhipicephalus sanguineus sensu lato were collected from the vegetation in three sample sites on a monthly interval.